2016
DOI: 10.1016/j.jpainsymman.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Dignity in Severe Chronic Obstructive Pulmonary Disease

Abstract: The prevalence of a problematic loss of dignity among patients with severe chronic obstructive pulmonary disease is at least as high as among those receiving palliative cancer care. Loss of dignity may represent a concern among people with medical illnesses more broadly, and not just in the context of "death with dignity" at the end of life. Furthermore, interdisciplinary care may help to restore a sense of dignity to those individuals who are able to participate in rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…Up to 1 in 10 people with COPD report a loss of dignity; 'the quality or state of being worthy, honoured, or esteemed', which in cross-sectional studies is associated with requiring assistance to self-care, anxiety and depression, and being uncertain about future health care. [42][43][44]…”
Section: Common Experiences Of Advanced Copdmentioning
confidence: 99%
“…Up to 1 in 10 people with COPD report a loss of dignity; 'the quality or state of being worthy, honoured, or esteemed', which in cross-sectional studies is associated with requiring assistance to self-care, anxiety and depression, and being uncertain about future health care. [42][43][44]…”
Section: Common Experiences Of Advanced Copdmentioning
confidence: 99%
“…27 In one study, about 13% of patients with severe COPD reported a loss of dignity that was correlated with anxiety and depression but not lung function. 25 Community dwelling palliative home care patients experiencing dyspnea were more likely to show overall signs of distress. 2 Dyspnea appears to be directly related to anxiety and depression, because by improving symptoms of shortness of breath, rates of anxiety and depression also improved in the same patient.…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 98%
“…Multilayered distress exemplifies the complex presence of physical, psychological and existential distress (Albers et al, 2013;Chochinov et al, 2016;Solomon et al, 2016), stemming from loss of the sense of self (Monaro et al, 2014), bodily changes evident to others, and changes in one's appearance (Olsson et al, 2008;Solomon et al, 2016). These individuals also reported feeling ashamed, degraded, or embarrassed because of the stigma from their medical problems (Solomon et al, 2016).…”
Section: Multilayered Distressmentioning
confidence: 99%
“…Negotiating mutual understanding (Sellars et al, 2018), approaching patients as wholly worthwhile individuals (van Gennip et al, 2015), encouraging autonomy and its interplay (van Gennip et al, 2015) and providing respectful and attentive communication (Tong et al, 2014) brought about a continuation of reciprocal relations. Continuation of social support occurred by assisting individuals with chronic progressive diseases: (a) to encourage patients to participate in family and social activities to fight isolation and loneliness (Skuladottir & Halldorsdottir, 2011); (b) through facilitating participation in support groups for patients and families (Monaro et al, 2014); (c) to establish appropriate interdisciplinary care (Solomon et al, 2016) and (d) through providing good professional care and social support (Oosterveld-Vlug et al, 2014). Continuation of individualized care was fostered by: (a) being attentive, proactive and taking the individual seriously (van Gennip et al, 2015); (b) supporting adjustment to their new way of life (Monaro et al, 2014), and (c) continuing to maximize function and independence (Reuben et al, 2013).…”
Section: Continued Relationshipmentioning
confidence: 99%